Eksplorasi NIM dan LDR terhadap Harga Saham dengan Mediasi NPL - Wulandari, Nisa Amelia; Firdaus, Firdaus; Nurhayati, Nurhayati; Suharti , Suharti (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study will look at how stock prices with non-performing loans (NPL) are affected by Net interest margin (NIM) and Loan to Deposit Ratio (LDR).Methodology/approach: This study uses secondary data from IDX for conventional banks in Indonesia from 2019 to 2023. This study uses the documentation method and analysis tools with the SEM-PLS approach.Results/findings: The results show that NPL is negatively and significantly affected by NIM, but NPL is not significantly affected by LDR, NIM is able to positively and significantly affect stock prices, but stock prices are not significantly affected by LDR. NIM has a positive and significant impact due to the mediating role of NPL. On the other hand, there is no significant impact between LDR and stock price with NPL mediation.Conclusions:Limitations: This study only uses the variables NIM, LDR, NPL and stock prices with a sample of 20 conventional banks listed on the IDX with annual reports for the period 2019 - 2023. Future research should be able to provide additional variables with a larger number to determine the effect on stock prices such as the use of financial ratios ROA, ROE, and external assets. In addition, it is also necessary to increase the number of samples used so that statistics can accurately represent the population such as using additional samples from Islamic banking, regional banking, or other industrial companies.Contribution: Stakeholders can use these results to assess the share price of the banking sector using financial ratios.